Synthesis of N-heterocyclic carbene stabilized catecholatoborenium cations by ligand substitution - Do, Dinh Cao Huan (2014)
Ligand substitution is not a common procedure for the preparation of different borenium cations. This work demonstrates that the chloride ligands of several NHC-stabilized dichloroborenium cations [NHC·BCl2][X] (NHC = (R′C)2(NR)2C; 1, R = iPr, R′ = H; 2, R = iPr, R′ = Me; 3, R = tBu, R′ = H; X = AlCl4, B(3,5-Cl2-C6H3)4) could be replaced with a catecholato moiety to produce [NHC·Bcat][X]. According to single-crystal X-ray analyses this particular ligand exchange enhanced the Lewis acidity of the target borocations with respect to the dichloro precursors.